2017
DOI: 10.1186/s12911-017-0471-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for pressure ulcers from intensive care unit electronic health records using Bayesian networks

Abstract: BackgroundWe develop predictive models enabling clinicians to better understand and explore patient clinical data along with risk factors for pressure ulcers in intensive care unit patients from electronic health record data. Identifying accurate risk factors of pressure ulcers is essential to determining appropriate prevention strategies; in this work we examine medication, diagnosis, and traditional Braden pressure ulcer assessment scale measurements as patient features. In order to predict pressure ulcer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 33 publications
(25 reference statements)
2
81
0
Order By: Relevance
“…Bayesian networks can represent complex relationships among variables involved in a disease process. Previous studies have shown that Bayesian networks can be used to assist diagnosis in a variety of diseases, such as breast cancer, hepato-biliary diseases, liver disorder, pneumonia, and pressure ulcer [20,[24][25][26][27]. Our study also demonstrated that BN models can be effectively applied for dengue diagnosis.…”
Section: Discussionsupporting
confidence: 56%
“…Bayesian networks can represent complex relationships among variables involved in a disease process. Previous studies have shown that Bayesian networks can be used to assist diagnosis in a variety of diseases, such as breast cancer, hepato-biliary diseases, liver disorder, pneumonia, and pressure ulcer [20,[24][25][26][27]. Our study also demonstrated that BN models can be effectively applied for dengue diagnosis.…”
Section: Discussionsupporting
confidence: 56%
“…Bayesian networks are very popular for capturing the uncertain knowledge in medicine and have been extensively used in the diagnosis of diseases. [12][13][14] The tree augmented naive (TAN) Bayesian network is a specific class of Bayesian networks used for classification problems and applied widely in health care. 15 The TAN Bayesian networks perform better than alternate classifiers when biomarkers are correlated, and at the same time maintain the mathematical simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…The project detecting and quantifying new and redundant information over longitudinal clinical notes presented by Zhang et al discussed an automated technique with statistical language models to improve data quality [9]. Kaewprag et al [10] explored a predictive analysis of pressure ulcer in intensive care unit patient records, which helps clinicians identify relationships between risk factors associated with pressure ulcers.…”
Section: Summary Of Selected Papers In the Thematic Issuementioning
confidence: 99%
“…These papers cover a wide range of topics including Knowledge and Data Personalization [1,2], Social Media Applications to Healthcare [3,4], Clinical Natural Language Processing [5,6], Patient Safety Analyses [7,8], and Data Mining Using Electronic Health Records [9,10].…”
Section: Summary Of Selected Papers In the Thematic Issuementioning
confidence: 99%
See 1 more Smart Citation